The Role of Disturbance Factors during Configuration of the Optimal Supply Chain in the Pharmaceutical Industry: A Conceptual Model - Huq, Fahian Anisul/FAH (2011)
In an atmosphere of declining R&D productivity, increase pricing pressure and changing regulatory requirements, pharmaceutical MNCs are under increasing challenges to improve profit margins by global outsourcing of R&D and manufacturing. Through the trends of globalisation and outsourcing, the complexity of the pharmaceutical supply network has increased and it has been increasingly exposed to SC disturbances. This has led to calls for changes to the structure of the modern pharmaceutical SC and is causing firms to rethink and redesign their SC. For these reasons, this study aims is to build a framework to identify all the important disturbance factors affecting the pharmaceutical SC; which can be later used to run simulations in order to gauge the performance of the different possible SC configurations. An extensive literature review and in-depth semi-structured interviews were the methods used in support of this work. First, three possible SC configurations that are available to European based pharmaceutical MNCs (focal company) is conceptualised. Next, the SC disturbance framework is developed, which is a tool that can be used to increase visibility of the disturbances that actors in a supply network are exposed to, or might potentially become exposed to, and to help in the assessment and management of those disturbances. The SC disturbance framework incorporates endogenous (firm related), exogenous (network related) and environmental (site related) disturbance factors; and suggests appropriate performance measures for the possible SC network configurations. Finally, a modelling approach to support strategic decision makers is created and a tool for solving the complex problem of SC configuration presented. This is called the SC configuration model, the novelty of which lies in the integration of SC design strategy and the degree of disturbance present in the SC. From the practical point of view, this research has contributed to the better understanding of how to identify disturbances along the SC and it suggests what strategies to choose while designing the optimal SC configuration, given the degree of disturbance. From a theoretical point of view, this study contributes to the research on supply chain risk management by providing a detailed conceptual framework of the supply chain disturbance constructs. It has also advanced the understanding of how to model and analyse the SC strategies and contributed to theory development in the emerging field of Supply Chain Management.